De Novo Fibrillary Glomerulonephritis (FGN) in a Renal Transplant with Chronic Hepatitis C - Edward J. Filippone; Christine Chmielewski; Rakesh Gulati; Eric Newman; John L. Farber (Case Reports in Transplantation)
Chronic hepatitis C viremia (HepC) has been associated with numerous renal manifestations both in native kidneys and in the setting of renal transplantation. Glomerulonephritis (GN) of the renal allograft in the setting of HepC most commonly manifests as type 1 membranoproliferative GN (MPGN), either representing recurrence of the original disease or arising de novo. Other GNs were reported after transplantation in the patient with HepC including membranous nephropathy and thrombotic microangiopathy, as well as an enhanced susceptibility to transplant glomerulopathy. We describe the first case of de novo fibrillary GN in a renal transplant patient with HepC where the primary renal disease was biopsy proven type 1 MPGN. We discuss this relationship in detail.